Bonsai and their risk for plant health: The case of the oriental tea tortrix Homona magnanima Diakonoff, 1948 - Gritta Schrader; Stephanie Feltgen; Matthias Becker; Olaf Zimmermann; Sibylle Rumsey; Gabriele Zgraja; Jörg Schaller; Ernst Pfeilstetter; Stephan König; Frederik Stein; Björn Hoppe (Journal für Kulturpflanzen)
The Oriental tea tortrix Homona magnanima Diakonoff, 1948 (Lepidoptera: Tortricidae) has been intercepted three times in Germany on imported plants from Japan since 2023. The moth was found on bonsai of Taxus sp., T. cuspidata and Pinus thunbergii. The findings were diagnosed in a close cooperation between official laboratories in the federal states of Baden-Wurttemberg (Landwirtschaftliches Technologiezentrum Augustenberg), Brandenburg (Landesamt für Ländliche Entwicklung, Landwirtschaft und Flurneuordnung), North Rhine-Westphalia (Landwirtschaftskammer) and the National Reference Laboratory located at Julius Kühn Institute (NRLJKI). DNA barcoding of the COI gene region revealed identical sequences for all findings in Germany. However, the final confirmation by a database comparison with NCBI GenBank and the BOLD database was insufficient, presumably due to incorrectly referenced but also missing entries. Phylogenetic analysis in combination with information on native distribution, host tree preferences and morphological features allowed for a species assignment as Homona magnanima. Following the identification, an Express-Pest Risk Analysis was conducted by the JKI, resulting in a categorisation of the tortrix as a potential quarantine pest.